A pragmatic guide to competency : tools, frameworks and assessment - Holt, Jon (Online access with subscription: Proquest Ebook Central., 2011)
Competency is the ability of an individual to perform their working activities. Competencies should be based on roles, rather than on job descriptions. This book shows how to assess competency in practical and effective ways to deliver productive organisations. Essential reading for IT managers and directors, consultants, and team leaders.